2014
DOI: 10.1186/s12955-014-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neuropathic pain and other comorbidities on the quality of life in patients with diabetes

Abstract: BackgroundDiabetic polyneuropathy (DPN) is one of the most common complications of diabetes and can exist with or without neuropathic pain. We were interested in how neuropathic pain impairs the quality of life in diabetic patients and what is the role of comorbidities in this condition.MethodsThe study included 80 patients with painful DPN (group “P”) and 80 patients with DPN, but without neuropathic pain (group “D”). Visual analogue scale (VAS) and Leeds assessment of neuropathic symptoms and signs (LANSS) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
5
32
1
1
Order By: Relevance
“…Furthermore, we found a significant worsening in all domains of SF-36 in patients with painful diabetic neuropathy confirmed with abnormal electrophysiological evaluation results, in particular. Suggesting our results, a previous study revealed statistically significant lower values in patients with PDN in all domains of SF-36 [25]. Some other studies demonstrate a significant alteration in physical, mental and general health components of OQL in patients with PDN [26].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we found a significant worsening in all domains of SF-36 in patients with painful diabetic neuropathy confirmed with abnormal electrophysiological evaluation results, in particular. Suggesting our results, a previous study revealed statistically significant lower values in patients with PDN in all domains of SF-36 [25]. Some other studies demonstrate a significant alteration in physical, mental and general health components of OQL in patients with PDN [26].…”
Section: Discussionsupporting
confidence: 89%
“… 18 Likewise, painful diabetic polyneuropathy significantly affects various aspects of the quality of life, including sleep disorders. 19 Similar to these studies, we observed a statistically significant change in pain severity after the 2-year follow-up in patients who manifested co-morbid illness compared to those who did not manifest a comorbidity. Therefore, the physician should be vigilant and regularly screen these high-risk patients for depression or other psychiatric illness, especially when a change in pain symptoms or functional impairment is noticed.…”
Section: Discussionsupporting
confidence: 87%
“…49 , 65 , 75 Animal studies mostly rely on stimulus-evoked measures of sensory gain, whereas clinical trials use patient-reported outcomes focusing on spontaneous pain intensity, functioning, and quality of life. Although spontaneous pain and decreased quality of life are reported across chronic pain conditions, 11 , 16 , 52 , 56 sensory gain is common only in a subset of clinical pain conditions caused by peripheral nerve trauma and inflammation but is rare in others, such as polyneuropathies caused by diabetes and HIV. 39 , 51 , 52 , 56 This has brought into question the translational strength of relying on sensory gain as the sole pain outcome measure preclinically.…”
Section: Introductionmentioning
confidence: 99%